2022
DOI: 10.1002/cne.25432
|View full text |Cite
|
Sign up to set email alerts
|

Cortical synapses of the world's smallest mammal: An FIB/SEM study in the Etruscan shrew

Abstract: The main aim of the present study was to determine if synapses from the exceptionally small brain of the Etruscan shrew show any peculiarities compared to the much larger human brain. We analyzed the cortical synaptic density and a variety of structural characteristics of 7,239 3D reconstructed synapses, using using Focused Ion Beam/Scanning Electron Microscopy (FIB/SEM). We found that some of the general synaptic characteristics are remarkably similar to those found in the human cerebral cortex. However, the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 93 publications
2
2
0
Order By: Relevance
“…In L1 and L3, we found synaptic densities of 1.80 and 1.08 synapses/µm 3 , respectively, that is, clearly lower than in the SR. These data are in line with the synaptic densities described in the somatosensory cortex of the Etruscan shrew 53 . In the somatosensory cortex of the juvenile rat, the synaptic densities are lower, but the proportion of excitatory and inhibitory synapses is similar to the mouse data, including the fact that layer 1 has a higher percentage of inhibitory synapses than layer 3 54 , 55 .…”
Section: Discussionsupporting
confidence: 90%
“…In L1 and L3, we found synaptic densities of 1.80 and 1.08 synapses/µm 3 , respectively, that is, clearly lower than in the SR. These data are in line with the synaptic densities described in the somatosensory cortex of the Etruscan shrew 53 . In the somatosensory cortex of the juvenile rat, the synaptic densities are lower, but the proportion of excitatory and inhibitory synapses is similar to the mouse data, including the fact that layer 1 has a higher percentage of inhibitory synapses than layer 3 54 , 55 .…”
Section: Discussionsupporting
confidence: 90%
“…We found that the majority of synapses had a macular shape (79–87%) and were the smallest synapses. These findings are in line with previous reports in other brain regions and species (Geinisman et al, 1987; Jones et al, 1991; Neuman et al, 2016; Hsu et al, 2017; Calì et al, 2018; Santuy et al, 2018a; Domínguez-Álvaro et al, 2019, 2021a; Montero-Crespo et al, 2020; Cano-Astorga et al, 2021, 2023; Turégano-López, 2022; Alonso-Nanclares et al, 2023). It has been reported that complex-shaped synapses possess more AMPA and NMDA receptors than macular synapses, characterizing them as a potentially ’powerful’ population associated with more enduring memory-related functionality than macular synapses (Geinisman et al, 1987, 1991, 1992a, 1992b, 1993; Lüscher et al, 2000; Toni et al, 2001; Ganeshina et al, 2004a, 2004b; Spruston 2008).…”
Section: Common Synaptic Characteristicssupporting
confidence: 93%
“…However, this characteristic is often misinterpreted as implying that synapses on dendritic shafts are mostly SS (Motta et al, 2019;Karimi et al, 2020;Loomba et al, 2022). In fact, quantitative analyses of synapses in the neuropil have shown that most synapses on dendritic shafts are AS (∼80%), with relatively few being SS (∼20%) (Beaulieu et al, 1992;Peters et al, 2008;Hsu et al, 2017;Calì et al, 2018;Santuy et al, 2018b;Domínguez-Álvaro et al, 2019Domínguez-Álvaro et al, , 2021aYakoubi et al, 2019b;Montero-Crespo et al, 2020Cano-Astorga et al, 2021, 2023Alonso-Nanclares et al, 2023). Therefore, synaptic organization datasets with incorrect assumptions regarding SS identification could introduce an important source of bias.…”
Section: Discussionmentioning
confidence: 99%
“…The most noticeable distinction lies in the postsynaptic density: AS have a thick postsynaptic density, while SS have a thin postsynaptic density. In general, regarding all synapses in the neuropil of the cerebral cortex, AS outnumber SS approximately 95:5 (see Alonso-Nanclares et al, 2023, andCano-Astorga et al, 2023, and the references therein). Importantly, it has been demonstrated that, in the cerebral cortex, most AS are excitatory (glutamatergic), while SS are inhibitory (GABAergic) (Colonnier, 1968;Gray, 1969;Peters and Kaiserman-Abramof, 1969;Houser et al, 1984;Peters and Palay, 1996;Ascoli et al, 2008).…”
Section: Introductionmentioning
confidence: 99%